Bentuk-Bentuk Mitos dan Tanggapan Siswa SMA Muhammadiyah 1 Surakarta Terhadap Mitos dalam Cerita Pendek Harimau Belang Karya Guntur Alam: Kajian Resepsi Sastra - Rahayu, Yuli Tri; , Dra. Main Sufanti, M.Hum (2017)
Abstract This research aims to describe the elements which build the short story written by Guntur Alam, to describe the types of myth in the short story 'Harimau Belang' written by Guntur Alam, and to describe the responses of the students on the myth in the short story 'Harimau Belang' written by Guntur Alam. Data of this research are in the forms of sentences in the short story and the information in the forms of the students' responses about the short story. The sources of the data in this research are the book of short story and the students who had read the short story. Type of this research is a desriptive qualitative research. Objects of this research are the structure, the forms of the myth, and the students' responses on the myth in the short story 'Harimau Belang' written by Guntur Alam. The technique of data collection was conducted using questionnair. The questionnair was completed by the studnets of SMA Muhammdiyah 1 Surakarta. The results of this research were obtained based on the problems statements which covered (1) The elements which build the short story 'Harimau Belang' written by Guntur Alam including theme, character, setting, and plot. The theme of this short story ini is the myth is not always true, (2) The types of the myth in the short story 'Harimau Belang' written by Guntur Alam are: first, harimau belang (a stripe tiger) is sacred and must not be disturbed; second, if a wife is pregnant, her husband must not disturb any animal or kill it; and (3) The students' responses on the first myth are: 100% of the students understood that the story contains myth, meanwhile, in the daily life, 100% of the students did not believe in the myth of the stripe tiger as contained in the story they read. The students' responses on the second myth: 80% of the students understood that the story contains myth, and 20% of the students said that the short story did not contain any myth. In the recent fact, 70% of students said that they did not believe in the existence of myth about the prohibition for a husband from disturbing animal and 30% of the rest said that they believe in such myth.